Analisis Implementasi Unit Kegiatan Belajar Mandiri (UKBM) Berintegrasi Kurikulum Berbasis Cinta dalam Peningkatan Assesmen Sumatif Pembelajaran Bahasa Indonesia di MAN 3 Kediri - Mayada Mayada; Arisni Kholifatu Amalia Shofiani (Institut Nalanda, 2026)
Education continuously strives to integrate and adapt to changing times. This study aims to analyze the implementation of Self-Learning Activity Units (Unit Kegiatan Belajar Mandiri or UKBM) integrated with a love-based curriculum to enhance summative assessment in Indonesian language learning at MAN 3 Kediri. This study employed a descriptive qualitative method. The data source for this research was a questionnaire distributed to students of MAN 3 Kediri as respondents. The data analysis technique used was qualitative with a narrative study approach, oriented toward describing the observations obtained from the distributed questionnaires. The results of the analysis revealed that the learning process at MAN 3 Kediri fully utilizes UKBM modules as supporting learning materials. Over time, the Indonesian language UKBM has integrated with a love-based curriculum. This integration includes the inculcation of five aspects of Panca Cinta (Five Loves). The Panca Cinta in question comprises: first, love for God, which encourages students to blend religious values into literary texts. Second, love for fellow human beings, which encourages students to develop critical thinking and empathy toward others. Third, love for knowledge, which motivates students to cultivate a passion for reading and writing. Fourth, love for the environment, to intensively analyze the relationship between language texts and their surrounding explanations. Fifth, love for the homeland, which is oriented toward upholding nationalistic values within Indonesian language texts.